Impact Of Different Ultrasonic Frequencies On Precipitation Process Of Dicalcium Phosphate Dihydrate Coated Hydroxyapatite Granular Surfaces - Fadzil Akmar, Nur Humairah (Universiti Sains Malaysia, 2022)
This project presents the fabrication of DCPD-coated HAP granules using the dissolution-precipitation method with the aid of sonication of single frequency (360kHz) and double frequency (32/158kHz) using the ultrasonic machine (crest ultrasonic). The new bone formation rate for hydroxyapatite is relatively slow compared to the growth of the natural bone, especially in a large bone defect area. Therefore, DCPD layer coating is proposed on the surface of HAp granules to increase the new bone formation rate. A new approach on DCPD coating using ultrasonic technology to obtain a coating layer in a short period, low cost and effective compared to other methods that are time consuming and involve high temperature to obtain CaP coating layer. Several characterisation methods were carried out, such as X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), dissolution behaviours of calcium ions, and pH analysis. The results of characterisations showed that the amount of DCPD crystals precipitated on the HAp granule surface increased as the acidic calcium phosphate solution concentration increased for single and double frequencies. As the concentrations of acidic calcium phosphate increased (0.025M,0.050M,0.075M,0.100M), the DCPD formation also increased. However, single frequency produced higher DCPD formation than double frequency. Therefore, this study showed that the amount of DCPD coated on HAp granule surfaces could be regulated by changing the concentration of acidic calcium phosphate solution or type of ultrasonic frequency.